Toward a greater understanding of breast cancer patients’ decisions to discuss cancer related internet information with their doctors: An exploratory study - D’Agostino, Thomas A. (2012)
OBJECTIVE: To investigate differences between breast cancer patients who do and do not discuss cancer-related internet information (CRII) with their doctors. METHODS: 70 breast cancer patients completed questionnaires regarding internet use, discussions about CRII, and the doctor-patient relationship. RESULTS: No significant differences were noted across patient, disease, or visit characteristics, or physician reliance between those who intended to discuss CRII and those who did not. Patients who intended to discuss CRII rated significantly higher pre-consultation anxiety levels. No significant differences in satisfaction, anxiety reduction, or trust in physician were found between patients who had discussed and those who had not. Patients’ reasons for discussing or not discussing are detailed. CONCLUSION: Factors influencing patients’ decisions to discuss CRII are complex and differ from those identified as leading patients to seek internet information. Future research about internet discussions should investigate the impact of patients’ preferred role in treatment, the doctor-patient relationship, anxiety level, attributes of CRII, and physician trust. PRACTICE IMPLICATIONS: Understanding the characteristics of patients who do and do not discuss internet information is important given the impact internet information has on healthcare communication and the doctor-patient relationship, including the development of interventions aimed at improving such interactions.